A bovine papilloma virus vector with a dominant resistance marker replicates extrachromosomally in mouse and E. coli cells. - Matthias, P D (1983)
We describe the construction of a bovine papilloma virus-based vector (pCGBPV9) which contains a dominant selectable marker and replicates autonomously in both mouse and Escherichia coli cells. This vector contains the complete bovine papilloma virus genome, a ColE1 replication origin and a dominant selectable marker conferring resistance to kanamycin in bacteria and G418 in eukaryotic cells. A high number of G418R colonies are obtained after transfer of pCGBPV9 into mouse C127 cells. These G418R colonies contain vector DNA which replicates autonomously at approximately 10-30 copies per cell. The molecules are in most cases unrearranged and can be rescued into E. coli cells by bacterial transformation.